Kesulitan Menggenggam pada Proses Belajar Menulis dan Membaca Anak DCD - Rahmi Wardah Ningsih (Mitra Ash-Shibyan: Jurnal Pendidikan dan Konseling, 2020)
Although the learning process of writing involves all other supporting elements, such as stimulation from parents, the ability to coordinate fingers in grasping is a major aspect of the process. This study examines the causes of grasping difficulties as well as their relation to children's learning and writing processes. Analysis of this study using journal analysis. The findings show that Developmental Coordination Disorder (DCD) or poor motor skills are the main cause of difficulty grasping children. DCD levels were tested by Finger Tapping (FT), Curve Tracing (CT), and Paragraph Writing tests. Whereas 2 experimental tasks, Manik Threading and Per-Board were used to assess the FMS of reading children. This meta-analysis concludes that DCD influences the learning process of writing children and Fine Motor Performance is also related to the process of early reading for early childhood. Researcher's solution, recommends a comprehensive eye examination for children's eye and finger coordination and helps improve children's FMS, perform occupational therapy for children with DCD as well as continuous stimulus for children to train their fingers in the learning process of writing and early reading in children.